Children, families, and HIV/AIDS : psychosocial and therapeutic issues - Boyd-Franklin, Nancy; Steiner, Gloria L.; Boland, Mary G. (New York ; London : Guilford, 1995)
Section I: Introduction Rationale and overview of the book / Gloria L. Steiner, Nancy Boyd-Franklin and Mary G. Boland
Section II: The epidemiological and medical context
* The health care needs of infants and children: An epidemiological perspective / Mary G. Boland and James Oleske
* Neurological and neurodevelopmental functioning in pediatric HIV infection / Jennis Hanna and Mark Mintz
Section III: The psychosocial context: Psychosocial issues for different groups
* Cultural sensitivity and competence: African-American, Latino, and Haitian families with HIV/AIDS / Nancy Boyd-Franklin, Julia del C. Aleman, Michele M. Jean-Gilles and Sandra Y. Lewis
* HIV-relevant issues in adolescents / Jacqueline A. Bartlett, Steven E. Keller, Haftan Eckholdt and Steven J. Schleifer
* Women and HIV/AIDS / Julia del Aleman, Patricia Kloser, Theresa Kreibick, Gloria L. Steiner and Nancy Boyd-Franklin
Section IV: Therapeutic approaches with HIV-infected children and their families
* Family systems interventions and family therapy / Nancy Boyd-Franklin, Julia del Aleman, Gloria L. Steiner, Elizabeth W. Drelich and Bradley C. Norford
* The HIV-infected child in therapy / Sylvia W. Pollock and Cheryl L. Thompson
* Nonpharmacological pain management for children with HIV/AIDS: Working with hypnotherapeutic techniques / Marge Iurato Torrance, Olivia R. Lewis, Mary Ellen La Brie and Lynn Czarniecki
* Support group for children with HIV/AIDS / Katherine A. Gomez, Heidi J. Haiken and Sandra Y. Lewis
* Caretakers' support group / Theresa Kreibick
* Death and dying/bereavement and mourning / Nancy Boyd-Franklin, Elizabeth W. Drelich and Elena Schwolsky-Fitch
Section V: Service deliverers and systems issues
* A multisystems approach to service delivery for HIV/AIDS families / Nancy Boyd-Franklin and Mary G. Boland
* Caring for the professional caregiver / Nancy Boyd-Franklin and Mary G. Boland
* HIV/AIDS in the schools / Ann Silver Pozen
* Professional, ethical, and moral issues / Nancy Boyd-Franklin, Hazel Staloff and Patricia M. Brady
* Legal issues / David C. Harvey
Section VI: Research and public policy
* Psychosocial research concerning children, families, and HIV/AIDS: A challenge for investigators / Laurie N. Sherwen and Susan Tross
* HIV/AIDS and public policy: Recent developments / David C. Harvey
Bibliografija iza svakog poglavlja
Kazalo
Keywords: AIDS; djeca; psihosocijalni aspekti; terapijski pristup